Effects of a Low-Dose Spirulina/Turmeric Supplement on Cardiometabolic and Antioxidant Serum Markers of Patients With Abdominal Obesity - Gómez-Téllez, Arlene; Sierra-Puente, Diego; Muñoz-Gómez, Regina; Ibarra-Pitts, Amelia; Guevara-Cruz, Martha; Hernández-Ortega, Marcela; Gutiérrez-Salmeán, Gabriela (Frontiers in Nutrition, 2020)
Obesity is one of the greatest public health problems worldwide. It is associated with underlying low-grade inflammation, thus is a risk factor for the development of cardiometabolic alterations. Functional foods, such as spirulina and turmeric, in the form of nutraceutics have been considered to exert not only an antioxidant effect but also modulating mechanisms in the metabolic pathways underlying cardiometabolic disruptions. We aimed to study the effectiveness of supplementation with a Spirulina maxima / Turmeric longa mixture (266 mg / 156.6 mg) on body composition, lipemic and antioxidant status in patients with abdominal obesity. To achieve this, 43 patients were included (control group, n=21, and experimental, n=22), in a double blind randomized controlled trial. Both groups were daily supplemented, orally, for 12 weeks. After 3-months supplementation (altogether with individualized dietary management), both groups showed a decrease in body weight, fat mass, and abdominal circumference; however, no intergroup statistical differences were found. The same phenomenon was observed concerning biochemical metabolic markers; nevertheless, an obvious trend favoring spirulina/turmeric supplementation can be appreciated. Finally, both groups significantly increased their serum antioxidant status although the supplemented groups showed a 2-fold accrue vs. placebo.